The Long, Lingering Shadow: slavery, race, and law in the american hemisphere - ROBERT J. COTTROL (University of Georgia Press, 2013)
this book is an effort to broaden our current conversation on law and race. In the United States, the discussion on law and race has, in my view, tended to focus too narrowly on the American experience. Th is is perhaps understandable. Th e law in the United States has played a clear, undeniable role both in the construction of the American system of racial inequality and in the struggle to achieve equal rights. Any student educated in the United States â€” perhaps one who has simply taken the undergraduate survey course in American history or even one who only vaguely remembers the subject from high school â€” knows this history, at least in broad outline. Th e new nation that began with a ringing declaration â€œthat all men are created equalâ€ quickly adopted a constitution that protected slavery, most prominently in that documentâ€™s fugitive slave clause. Slavery had the lawâ€™s imprimatur, an imprimatur reinforced by the Supreme Courtâ€™s 1857 decision in Dred Scott v. Sandford â€” the infamous Dred Scott case. A cataclysmic civil war that killed more Americans than any of the nationâ€™s foreign confl icts put an end to slavery. Th e Constitution was amended in the wake of that confl ict. Th e new Th irteenth Amendment permanently prohibited slavery. Th e Fourteenth proclaimed the citizenship and equal status of the former slaves. Th e Fift eenth opened political rights â€” voting â€” to all men, regardless of race. Th e nation enjoyed, briefl y, that â€œnew birth of freedomâ€ eloquently proclaimed in Lincolnâ€™s Gettysburg Address. But by the end of the nineteenth century, the light of freedom was growing dimmer. Inequality was again being made part of the law of the land. State Jim Crow statutes mandating separate and stigmatizing treatment for Americans of African descent were declared constitutional by the Supreme Court in Plessy v. Ferguson in 1896. Th e stage was set for an early twentieth- century history of rigid segregation, racial violence, and disenfranchisement. Th e stage was also set for one of the more inspiring chapters in the legal history of the United States and indeed any nation, the struggle to use the law to dismantle the system of state- mandated inequality that prevailed in the southern states and indeed throughout the nation. Th at struggle would take many forms, bringing the champions of equal rights many times before the nationâ€™s courts and legislatures. Th e most important triumphs of the civil rights movement in the postwar era â€” the Supreme Courtâ€™s 1954 decision in Brown v. Board of Education, outlawing segregation in public education; the Civil Rights Act of 1964, outlawing discrimination in public accommodations and employment; and the 1965 Voting Rights Act prohibiting discriminatory practices against minority voters â€” remain the foundations of modern American antidiscrimination law.